Expression and Functional Analysis of the BCL2-Associated Agonist of Cell Death (BAD) Gene in the Sheep Ovary During the Reproductive Cycle - Cao, Xiaohan; Wang, Xiangyu; Lu, Lulu; Li, Xiaoyu; Di, Ran; He, Xiaoyun; Hu, Wenping; Zeng, Xianyin; Liu, Qiuyue; Chu, Mingxing (Frontiers in Endocrinology, 2018)
Most ewes in China are seasonally polyestrous with normal ovulatory cycles, which is controlled by photoperiod (length of the daily light phase). These ewes are estrous in the short-day season and anestrus in the long-day season and cannot mate during anestrus. Thus seasonal breeding limits both diversification and intensification of production. If sheep can estrus all round year, it can be mated twice per year, which can greatly improve the economic benefits. To change seasonal estrus at the genetic level and cultivating new sheep breeds, it is important to understand the molecular mechanisms of seasonal breeding trait in sheep. The BCL2-associated agonist of cell death (BAD) gene being a regulator of cellular apoptosis was identified by our previous RNA-Seq, which is associated with follicular development in mammalian ovaries. However, the mechanism how BAD can regulate estrus in sheep was poorly understood. In this study, we characterized ovine BAD, including full-length mRNA cloning and protein sequence prediction, as well as BAD expression profile in Small-tailed Han (STH) sheep. The highest expression levels of BAD were observed in sheep hypothalamus, lung and pituitary, while the lowest expression was in liver. Functional analysis of BAD was performed in primary granulosa cells of sheep. The concentration of P4 was significantly increased after RNAi interference of BAD, while P4 level was shown to be opposite after BAD overexpression in vitro. It has been found that BAD can reduce progesterone levels by promoting ovarian GC apoptosis, which might be involved in regulating the estrus cycle in sheep.